Innovation and invention in medical devices : workshop summary - Hanna, Kathi E. (Compass series (Washington, D.C.), 2001)
Material from a recent workshop is summarized here, examining the nature of innovation in the field and the social and economic infrastructure that supports innovation and invention in medical devices, identifying unmet clinical needs, and considering barriers to the application of new technologies to meet clinical needs.